Social Space and Public Aspiration in Village Policy Process A Case Study in Peron Village, Limbangan, Kendal, Indonesia - Muhammad, Muhammad; Al-Atas, Mohammad Ilham; Kholifah, Umi (Publica: Jurnal Pemikiran Administrasi Negara, 2024)
Public aspirations are essential in policy formulation in an ideal political system. Especially at the village level in Indonesia, many researchers argue that with the implementation of village funds, the implementation of participation at the village level can better capture public aspirations. However, in reality, efforts to absorb public aspirations in a participatory manner experience many obstacles. One important suspicion is that this public space may not be a comfortable and safe public space for people to express their aspirations. By using a mix method, this research explores alternative explanations based on empirical data that people tend to use their own social space as a safe and comfortable space for aspirations.